2015
DOI: 10.1016/j.nbd.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent KCNQ2 pore mutation causing early onset epileptic encephalopathy has a moderate effect on M current but alters subcellular localization of Kv7 channels

Abstract: Mutations in the KCNQ2 gene encoding the voltage-dependent potassium M channel Kv7.2 subunit cause either benign epilepsy or early onset epileptic encephalopathy (EOEE). It has been proposed that the disease severity rests on the inhibitory impact of mutations on M current density. Here, we have analyzed the phenotype of 7 patients carrying the p.A294V mutation located on the S6 segment of the Kv7.2 pore domain (Kv7.2(A294V)). We investigated the functional and subcellular consequences of this mutation and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 42 publications
7
79
1
Order By: Relevance
“…7b), as reported for native channels in rat neocortical neurons38. By contrast, Kv7.2 subunits carrying a different EE-associated variant affecting a pore residue (A294V) failed to localize at the AIS, as previously described39 (Fig. 7).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…7b), as reported for native channels in rat neocortical neurons38. By contrast, Kv7.2 subunits carrying a different EE-associated variant affecting a pore residue (A294V) failed to localize at the AIS, as previously described39 (Fig. 7).…”
Section: Resultssupporting
confidence: 85%
“…Epilepsy-causing mutations in Kv7.2 may interfere with such AIS targeting3940. To assess whether the Kv7.2 R325G mutation also prompted similar effects, wild-type or mutant Kv7.2 subunits were expressed (together with Kv7.3 subunits) by transient transfection in embryonic rat hippocampal neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mutations located within the S5-S6 or the C-terminal domains decrease M-current amplitude from a moderate (~25%) to a strong (>50%) level. 6,7 However, three reported mutations located in the S2 (p.R144Q) and S4 (p.R201C and p.R201H) regions of Kv7.2 actually increased M-current amplitude. 8 This suggested that EOEE mutations located in the voltage-sensing domain can be gain of function mutations.…”
mentioning
confidence: 93%
“…In these cases, Application of retigabine partially reversed these effects for the majority of analyzed mutations [5]. However, some mutations of KCNQ2 do not alter significantly the channel properties in term of current intensity, but either the expression of the channel, or even its localization within the neuronal membrane [6]. These alterations are obviously not corrected by retigabine.…”
Section: Retigabine and Kcnq2 Mutationsmentioning
confidence: 92%